Linking Patient Safety Culture to Quality Ratings in the Nursing Home Setting. (January 2022) - Yount, Naomi; Zebrak, Katarzyna A.; Famolaro, Theresa; Sorra, Joann; Birch, Rebecca
There is limited evidence on the associations between patient safety culture and measures of health care quality in nursing homes. This study examines the relationship between scores on the Agency for Healthcare Research and Quality (AHRQ) Surveys on Patient Safety Culture™ (SOPS®) Nursing Home Survey (NH SOPS) and Centers for Medicare and Medicaid Services Nursing Home Five-Star Quality Ratings. Using data from 186 nursing homes, we conducted multiple regression analyses predicting the Five-Star Quality Ratings from the NH SOPS survey measures. Five NH SOPS measures were related to the Overall, Health Inspections, and Quality Five-Star Ratings. Four NH SOPS measures were related to at least two of the four Five-Star Quality Ratings and three SOPS measures were related to one Five-Star Rating. None of the NH SOPS measures were significantly associated with the Staffing Five-Star Rating. Findings generally indicated that stronger patient safety culture is associated with higher quality ratings.